Leadership and Initiative in Late Republican and Early Imperial Rome - Frolov, Roman M.,; Demidov, P.G.,; Burden-Strevens, Christopher, (Mnemosyne, Supplements ;, 2022)
What does it mean to be a leader? This collection of seventeen studies breaks new ground in our understanding of leadership in ancient Rome by re-evaluating the difference between those who began a political action and those who followed or reacted. In a significant change of approach, this volume shifts the focus from archetypal "leaders" to explore the potential for individuals of different ranks, social statuses, ages, and genders to seize initiative. In so doing, the contributors provide new insight into the ways in which the ability to initiate communication, invent solutions, and prompt others to act resonated in critical moments of Roman history.